2018
DOI: 10.18203/2320-1770.ijrcog20181940
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of osteoporosis in hysterectomised as compared to non-hysterectomized women in 7th decade of life

Abstract: Background: Osteoporosis is considered as a major public health issue with fragility fractures of the hip, vertebrae and distal radius being the most important consequences. It has been said to be an age-related degenerative process. However, postmenopausal women develop this disease due to age-related bone mineral loss as well as due to declining levels of estrogen in the body following menopause leading to increased risk of fractures. Objectives of this study were to find out the prevalence of osteoporosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Osteopenia and osteoporosis was significantly higher with increasing number of years post hysterectomy which is in comparison with previous studies. [19][20][21] The bone loss increases with increasing years of postmenopausal women with 1-2.3% in first 5 years and 7-10% after 5 years thus increasing the chances of osteoporotic fractures. 15 The above results clearly showed that premenopausal women undergoing hysterectomy experience bone loss and especially in women who undergo oophorectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Osteopenia and osteoporosis was significantly higher with increasing number of years post hysterectomy which is in comparison with previous studies. [19][20][21] The bone loss increases with increasing years of postmenopausal women with 1-2.3% in first 5 years and 7-10% after 5 years thus increasing the chances of osteoporotic fractures. 15 The above results clearly showed that premenopausal women undergoing hysterectomy experience bone loss and especially in women who undergo oophorectomy.…”
Section: Resultsmentioning
confidence: 99%